Flavonoids, cytotoxic, antioxidant and antibacterial activities of Evax pygmaea. (1st January 2017) - Khalfallah, Assia; Berrehal, Djemaa; Bensouici, Chawki; Kabouche, Ahmed; Semra, Zahia; Voutquenne-Nazabadioko, Laurence; Alabdul Magid, Abdulmagid; Kabouche, Zahia
Abstract: Context: Phytochemical study and biological potential of Evax pygmaea (L.) Brot. (Asteraceae) are reported for the first time. Objective: To identify the secondary metabolites of Evax pygmaea and to determine its antioxidant, antibacterial and cytotoxic activities. Materials and methods: Dried aerial parts (1 kg) were macerated in 70% MeOH (5 L) during 72 h. The concentrated hydromethanolic extract was subjected to extractions with chloroform (3 × 300 mL), ethyl acetate (3 × 300 mL) and n -butanol (3 × 300 mL), successively. VLC of combined ethyl acetate (EAEP) and n -butanol (BEP) fractions was followed by column purifications. Antioxidant activity was investigated using DPPH, CUPRAC, and metal chelating, β-carotene/linoleic acid and ABTS assays. Agar method was used in the antibacterial study. Cytotoxic activity was determined by Brine shrimp lethality test in DMSO and ethanol, at varying concentrations (2, 1 and 0.2%) and (1, 0.2 and 0.1%) successively. Results: Quercetin (1 ), isorhamnetin 3- O -β-d -xyloside (2 ), isorhamnetin 3- O -β-d -glucoside (3 ), quercetin 3- O -β-d -glucoside (4 ), quercetin 7- O -β-D -glucoside (5 ), patuletin 3- O -β-d -glucoside (6 ) were isolated from for the first time from Evax genus. The EAEP was the most active in ABTS (IC50 : <3.125 μg/mL) assay whereas the BEEP exhibited the highest activity in the β-carotene/linoleic acid assay (IC50 : <3.125 μg/mL). The EAEP and BEP exhibited good antibacterial activity (MIC: 40–80 µg/mL). The plant did not show any toxicity (LD50 >80 µg/mL). Discussion and conclusions: Six flavonoids were isolated for the first time from Evax pygmaea which exhibited good antioxidant and antibacterial activities.